Suitability Of Nitisinone In Alkaptonuria 1 (SONIA 1): an international, multicentre, randomised, open-label, no-treatment controlled, parallel-group, dose-response study to investigate the effect of once daily nitisinone on 24-h urinary homogentisic acid excretion in patients with alkaptonuria after 4 weeks of treatment. Issue 2 (4th December 2014) - Ranganath, Lakshminarayan R; Milan, Anna M; Hughes, Andrew T; Dutton, John J; Fitzgerald, Richard; Briggs, Michael C; Bygott, Helen; Psarelli, Eftychia E; Cox, Trevor F; Gallagher, James A; Jarvis, Jonathan C; van Kan, Christa; et al.
Abstract : Background: Alkaptonuria (AKU) is a serious genetic disease characterised by premature spondyloarthropathy. Homogentisate-lowering therapy is being investigated for AKU. Nitisinone decreases homogentisic acid (HGA) in AKU but the dose-response relationship has not been previously studied. Methods: Suitability Of Nitisinone In Alkaptonuria 1 (SONIA 1) was an international, multicentre, randomised, open-label, no-treatment controlled, parallel-group, dose-response study. The primary objective was to investigate the effect of different doses of nitisinone once daily on 24-h urinary HGA excretion (u-HGA24 ) in patients with AKU after 4 weeks of treatment. Forty patients were randomised into five groups of eight patients each, with groups receiving no treatment or 1 mg, 2 mg, 4 mg and 8 mg of nitisinone. Findings: A clear dose-response relationship was observed between nitisinone and the urinary excretion of HGA. At 4 weeks, the adjusted geometric mean u-HGA24 was 31.53 mmol, 3.26 mmol, 1.44 mmol, 0.57 mmol and 0.15 mmol for the no treatment or 1 mg, 2 mg, 4 mg and 8 mg doses, respectively. For the most efficacious dose, 8 mg daily, this corresponds to a mean reduction of u-HGA24 of 98.8% compared with baseline. An increase in tyrosine levels was seen at all doses but the dose-response relationship was less clear than the effect on HGA. Despite tyrosinaemia, there were no safety concerns and no serious adverse events were reported over the 4 weeks of nitisinone therapy. Conclusions: In this study in patients with AKU, nitisinone therapy decreased urinary HGA excretion to low levels in a dose-dependent manner and was well tolerated within the studied dose range. Trial registration number: EudraCT number: 2012-005340-24. Registered at ClinicalTrials.gov: NCTO1828463.